Advances in Copper-Based Biomaterials With Antibacterial and Osteogenic Properties for Bone Tissue Engineering - Shen, Qiudi; Qi, Yansong; Kong, Yangzhi; Bao, Huricha; Wang, Yifan; Dong, Alideertu; Wu, Haixia; Xu, Yongsheng (Frontiers in Bioengineering and Biotechnology, 2022)
Treating bone defects coupled with pathogen infections poses a formidable challenge to clinical medicine. Thus, there is an urgent need to develop orthopedic implants that provide excellent antibacterial and osteogenic properties. Of the various types, copper-based biomaterials capable of both regenerating bone and fighting infections are an effective therapeutic strategy for bone tissue engineering and therefore have attracted significant research interest. This review examines the advantages of copper-based biomaterials for biological functions and introduces these materials’ antibacterial mechanisms. We summarize current knowledge about the application of copper-based biomaterials with antimicrobial and osteogenic properties in the prevention and treatment of bone infection and discuss their potential uses in the field of orthopedics. By examining both broad and in-depth research, this review functions as a practical guide to developing copper-based biomaterials and offers directions for possible future work.